ECONOMIC GOVERNANCE IN INDONESIA'S FREE TRADE EPOCH: NAVIGATING CHALLENGES, IMPLEMENTING STRATEGIES, AND CULTIVATING SUSTAINABLE PROSPERITY - Bahrun Thalib; Luckhy Natalia Anastasye Lotte; Eigis Yani Pramularso; Arie Fitria; Loso Judijanto (CV. Adiba Aisha Amira, 2025)
This study delved into the intricate dynamics of economic governance in Indonesia's free trade epoch, offering a comprehensive analysis of the nation's journey in navigating challenges, implementing strategies, and fostering sustainable prosperity. The historical evolution unfolded as a testament to Indonesia's adaptability, marked by a deliberate reduction in state-owned enterprises and a shift towards a market-oriented approach. Key institutions, including the Central Bank of Indonesia and the Financial Services Authority, emerged as stalwarts, steering the nation through economic challenges with finesse. The literature review synthesized key findings, revealing consistencies and inconsistencies in understanding the impact of free trade agreements. Challenges such as trade deficits and income inequality were scrutinized alongside institutional reforms, such as the Making Indonesia 4.0 roadmap. The review identified gaps, urging further exploration into regional variations and the nuanced intersectionality of economic, social, and environmental factors. Implications for economic governance highlighted the need for targeted policy interventions, inclusive economic policies, and a call for continuous research to refine strategies. Acknowledging limitations, the study concluded with a nuanced understanding of Indonesia's economic landscape, paving the way for informed governance in the nation's ongoing pursuit of sustainable prosperity.